Impact of the Qali Warma school feeding program on anemia and chronic malnutrition in children - Francke, Pedro Andrés (2020)
This article provides evidence of the impact of the Qali Warma school feeding program on anemia and chronic malnutrition in children between 3 and 5 years of age in Peru. Drawing on data from the 2014 to 2017 Peruvian Demographic and Health Survey, we obtain empirical results through a quantitative two-step evaluation. First, we use entropy balancing and machine learning techniques to achieve a comparable control group that allows for robust estimates. Then, employing regressions, we estimate the program’s effect  on the variables of interest. The results indicate that Qali Warma has no effect on anemia nor on chronic malnutrition in the age range studied.